2012
DOI: 10.1097/dad.0b013e31823fd8e4
|View full text |Cite
|
Sign up to set email alerts
|

“Onycholemmal Carcinoma.” An Unusual Case With Apocrine and Sebaceous Differentiation. Are These Tumors a Microcystic Nail Bed Carcinoma?

Abstract: Subungual malignant epithelial tumors with tricholemmal keratinization have rarely been described as "malignant proliferating onycholemmal cyst" and "onycholemmal carcinoma (OC)." We report an additional case of a slow growing OC occurring on the middle finger of a 58-year-old man, which was unusual as it showed sebaceous-apocrine differentiation, in addition to a nail bed carcinoma with tricholemmal microcysts. We therefore consider the descriptive term of microcystic nail bed carcinoma more appropriate than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Herein, we report a case of SCC of the nail unit with distinct features of the previously described variant, OC, presenting as a very rare slow-growing malignant tumor arising from nail bed epithelium [4]. Since it was first described by Alessi et al [4] in 2004, there have only been 15 previously reported cases in the English literature, which are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10]. Previously reported cases of OC have presented with varying clinical manifestations.…”
Section: Discussionmentioning
confidence: 92%
“…Herein, we report a case of SCC of the nail unit with distinct features of the previously described variant, OC, presenting as a very rare slow-growing malignant tumor arising from nail bed epithelium [4]. Since it was first described by Alessi et al [4] in 2004, there have only been 15 previously reported cases in the English literature, which are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10]. Previously reported cases of OC have presented with varying clinical manifestations.…”
Section: Discussionmentioning
confidence: 92%
“…Recognition of this entity is important to ensure that appropriate, but not excessively aggressive, management is pursued. Among Cases with reported treatments, nine of thirteen (69%) lesions were treated by amputation or distal interphalangeal joint disarticulation . One lesion was managed with radiation, one with Mohs surgery, and two with more conservative re‐excisions .…”
Section: Discussionmentioning
confidence: 99%
“…Among cases with reported treatments, nine of thirteen (69%) lesions were treated by amputation or distal interphalangeal joint disarticulation. [1][2][3][4][5]7,10 One lesion was managed with radiation, one with Mohs surgery, and two with more conservative re-excisions. 1 To date, none of the reported cases have recurred locally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onycholemmal carcinoma (OC), also called microcystic nail bed carcinoma, is a slow‐growing malignant epithelial tumor originating from the nail bed epithelium. Since the first description by Alessi et al only 12 other cases have been described in the English literature …”
mentioning
confidence: 99%